The effectiveness of insurer‐supported safety and health engineering controls in reducing workers' compensation claims and costs. Issue 12 (15th September 2014) - Wurzelbacher, Steven J.; Bertke, Stephen J.; Lampl, Michael P.; Bushnell, P. Timothy; Meyers, Alysha R.; Robins, David C.; Al‐Tarawneh, Ibraheem S.
<x xml:space="preserve">Abstract</x> Background This study evaluated the effectiveness of a program in which a workers' compensation (WC) insurer provided matching funds to insured employers to implement safety/health engineering controls. Methods Pre‐ and post‐intervention WC metrics were compiled for the employees designated as affected by the interventions within 468 employers for interventions occurring from 2003 to 2009. Poisson, two‐part, and linear regression models with repeated measures were used to evaluate differences in pre‐ and post‐data, controlling for time trends independent of the interventions. Results For affected employees, total WC claim frequency rates (both medical‐only and lost‐time claims) decreased 66%, lost‐time WC claim frequency rates decreased 78%, WC paid cost per employee decreased 81%, and WC geometric mean paid claim cost decreased 30% post‐intervention. Reductions varied by employer size, specific industry, and intervention type. Conclusions The insurer‐supported safety/health engineering control program was effective in reducing WC claims and costs for affected employees. Am. J. Ind. Med. 57:1398–1412, 2014. © 2014 Wiley Periodicals, Inc.